Moral behavior of resident assistants: a lived experience - Stark, Rachael H., author; Anderson, Sharon K., advisor; Banning, James, committee member; McKelfresh, David, committee member; Scott, Malcolm, committee member (Colorado State University. Libraries, 2013)
Resident Assistants (RAs) are traditionally upper-class students who are responsible for enforcing residence-hall policies (Heala, 2006). These undergraduate paraprofessional students are consistently asked to hold their peers accountable for their behavior, yet this task can be a struggle for those RAs who are unable to display consistently moral behavior. Although the literature is full of examples of higher education's lasting effects on students' moral development, little is known about the moral development of college students who are serving in the role of RA. Even less is known about moral behavior in the lived experience of RAs tasked with enforcing disciplinary policies. The purpose of this study was to explore the moral behavior in the "lived experience" of RAs who administer disciplinary policy. The research questions that formed the basis for this exploration were (a) What is the lived experience of RAs who administer disciplinary polices at a residential college in a large urban area? and (b) How can we understand RAs' lived experience using the theoretical lens of Rest's model of moral behavior? The research method for this study was interpretative phenomenological analysis (IPA). The analysis consisted of 12 total interviews with a group of students who comprised one sophomore, six juniors, four seniors, and one fifth-year senior who served as RAs within the University Housing and Residential Life department at a large-size, public, urban institution located in the Mid-Atlantic region of the United States. The results of the study suggest that a majority of RAs interviewed did not demonstrate all four components of Rest's model of moral behavior: (a) moral sensitivity, (b) moral judgment, (c) moral motivation, and (d) moral character when they were confronting policy violations in the residence halls (Rest, 1986). Their reasons for not displaying moral behavior included their relationships with residents and specific decision-making factors that led to their not following through on their positional responsibilities as they had been trained to do. Two of the RAs interviewed were prototypical and consistently displayed all four components of Rest's model of moral behavior.
Keywords: James Rest; resident assistants; moral behavior